Development Status of Auto-cascade Refrigeration Technology - Liu Pengpeng; Sheng Wei; Jiao Zhongyan; Gao Xuyang (Zhileng xuebao)
As a refrigeration technology with wide-temperature district, auto-cascade refrigeration has a very broad application prospect in the refrigeration and cryogenic field. Compared with single stage compression, two stage compression and cascade refrigeration technology, the advantages and characteristics of auto-cascade refrigeration technology are pointed out after the principles and application of auto-cascade refrigeration technology are introduced. Mainly from auto-cascade refrigeration technology process and mixed refrigerant selection and proportion, the current research situation of auto- cascade refrigeration technology is analyzed, and the technology development trends of the design of system process and mixed refrigerant selection and proportion are pointed out. This paper provides a reference of the technology for further development and application.